The Influence of Competence, Motivation and Career Development on Nurse Performance Mediated by Organizational Commitment at Dr.Tc.Hillers Maumere Regional General Hospital - Onang, Yuliana; Djawoto, Djawoto; Prijati, Prijati (UNIVERSITAS PAKUAN, 2023)
This study aims to determine the effect of competence, motivation and career development on the performance of nurses mediated by organizational commitment at the Regional General Hospital dr.TC.Hillers Maumere. The aim of the study was to analyze the influence of competence, motivation and career development on nurse performance mediated by organizational commitment at Dr TC Hillers Maumere Hospital. The population in this study were ninety-five nurses with clinical nurse qualification III. The sampling technique used was purposive sampling. Data collection techniques using a questionnaire. The data analysis technique used is descriptive statistical analysis with SPSS software tools and inferential statistics using Smart PLS 3.0. The test results show that competence, motivation and career development have a positive and significant effect on nurse performance. However, competency, motivation and career development mediated by organizational commitment show a positive and insignificant effect on nurse performance